ASSESSING THE IMPACT OF EMPLOYEE WELLNESS PROGRAMS ON HEALTHCARE EMPLOYEE’S WEIGHT - (:unkn) unknown (My University, 2023)
Introduction: Over 32% of employees in healthcare are clinically overweight with a BMI over 30. This level of obesity is more significant in healthcare than in other professions. (Aldana, 2021). The growing prevalence of diseases among employees in healthcare settings has increased the concern about their health, well-being, and productivity. (Aldana, 2021). Notably, the reduction of obesity rates holds the potential to avert 40 million instances of chronic diseases, encompassing hypertension, diabetes, and cardiovascular ailments. (Milken Institute Study, 2022) Therefore, maintaining a healthy body weight or shedding excess pounds is crucial to reduce the risk of developing these. As a response, employers are adopting employee wellness programs to proactively prevent illnesses or identify and address health issues early, preventing complications. One way to prevent health issues would be to have a strategic focus that involves addressing obesity being the root cause of numerous chronic diseases. This research aims to assess the impact of Advocate Aurora’s healthy living programs Weight Watchers (WW), Health Management Resources (HMR), Healthy Habits, and Noom in comparison to their new added “Foodsmart” program on weight loss among overweight/obese employees measured by BMI (Body Mass Index). The findings of this research seek to determine the effectiveness of employee wellness programs (EMPs) on weight loss and overall health and well-being, providing recommendations for future research. This study aims to contribute to the existing literature on holistic health, wellness promotion/education, and behavioral economics. This study will employ the use of two theoretical approaches to explain the patterns of participation in the EWPs: the self-care deficit theory, and behavioral economics theories, specifically present bias, and nudging.Methods: This is a retrospective study, analyzing participants in Advocate Aurora's recent healthy living program, "Foodsmart," and comparing them with participants from their other wellness programs. The examination will encompass demographic differences among Foodsmart participants and participants in alternative wellness programs. Additionally, it will assess changes in BMI among participants in employee wellness programs from 2022 to 2023. Result: Out of the 6,708 healthcare workers, 595 engaged in Foodsmart, 1,635 in Weight Watchers (WW), 3,290 in Noom, 438 in Healthy Habits, and 230 in Health Management Resources (HMR). The Foodsmart program demonstrated a minor reduction in the average BMI from 31.8 to 31.6 post-intervention, indicating a slight positive impact on participants' weight status (-0.2). Similarly, HMR participants exhibited a slight decrease in average BMI from 32.5 in 2022 to 32.3 in 2023 (-0.2). In contrast, WW, Healthy Habits, and Noom recorded slight increases in average BMI post-intervention (0.1-0.2). The collective average BMI for all programs in 2022 was 33.12, experiencing a marginal uptick to 33.14 in 2023 post-intervention. Despite being a minimal increase, it implies that, on average, there was a minor alteration in participants' BMI due to involvement in EWPs. Although the statistical analysis indicates no significant change, it is crucial to consider practical significance. The slight rise in average BMI may not reach statistical significance, yet it suggests that, on average, there was no improvement in participants' BMI following the intervention.
Keywords: Behavioral economics; Employee wellness programs; Food as medicine; Healthcare employees; Holistic health and wellness; Wellness promotion